Indirect Evolution versus Strategic Delegation: A Comparison of Two Approaches to Explaining Economic Institutions - Martin Dufwenberg; Werner Güth (Uppsala University, Department of Economics, 1998)
Two major methods of explaining economic institutions, namely by strategic choices or through (indirect) evolution, are compared for the case of a homogenous quadratic duopoly market. Sellers either can provide incentives for agents to care for sales, or evolve as sellers who care for sales in addition to profits. The two approaches are conceptually quite different, yet similar in the sense that both allow certain kinds of commitment. We show that when the two models are set up in intuitively comparable ways strategic delegation does not change the market results as compared to the usual duopoly solution, while indirect evolution causes a more competitive behavior. Thus the case at hand underscores the differences between the two approaches in explaining economic institutions.
urn:nbn:se:uu:diva-2415
Keywords: C72; D21; D43; 330; Indirect evolution; strategic delgation; commitment; duopoly markets; agency theory